HR Analytics as an HR Auditing Technique to Evaluate the Effectiveness of Human Resources Practices - Patil, Akshat (Journal of Advanced Research in HR and Organizational Management, 2022)
This study paper focuses on HR Analytics as a tool of HR Auditing and its influence on organizational performance and the competitiveness of enterprises. Over the course of the last three to four years, businesses have begun to implement analytics systems across a variety of their operational domains in response to the expanding impact of globalization and technology. One of the divisions deals with the management of the available human resources. Therefore, it is obligatory to know your manpower, their competence, talents, and capacity to conduct job using HR Analytics. Reviewing and aligning the workforce is extremely vital to assess Return on Investment (RoI). As a result, HR Analytics is an essential tool in the HR Audit system. This tool is highly important not only for the organization as a whole but also for the development of individuals working in the organization. HR Analytics has the potential to drive a variety of different HR tasks, including workforce planning, scheduling, incentive schemes, salary estimations, pay budgeting, and employee relations. It provides valuable insights for general managers and HR leaders, allowing them to make key talent decisions, compensation systems, organizational design, and allocation of HR analytics for training budgets as a “must have” capability to ensure that HR analytics as a “must have” capability that will ensure HR’s future as a strategic management function while simultaneously transforming organizational performance for the better levels.